Stroke prevention in atrial fibrillation: An Asian perspective - Chiang, Chern-En; Wang, Kang-Ling; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2014)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. In 2050, it is estimated that there will be 72 million AF patients in Asia, accounting for almost 2.9 million patients suffering from AF-associated stroke. Asian AF patients share similar risk factor profiles as non-Asians, except that more Asians have a history of previous stroke. Clinical challenges are evident in the field of stroke prevention in AF, amongst Asians. Existing stroke and bleeding risk scores have not been well-validated in Asians. Asians are prone to bleeding when treated with warfarin, and the optimal international normalised ratio (INR) for warfarin use is yet to be determined in Asians, though Asian physicians tend to keep it in a lower range (e.g. INR 1.6–2.6) for elderly patients despite limited evidence to justify this. In general, warfarin is ‘difficult’ to use in Asians due to higher risk of bleeding and higher stroke rate in Asians than in non-Asians, as shown in randomised controlled trials. Excess of bleeding was not found in Asians when novel oral anticoagulants (NOACs) were used. Besides, the superiority of NOACs to warfarin in reducing thromboembolism was maintained in Asians. Therefore NOACs are preferentially indicated in Asians in terms of both efficacy and safety. Also, some preliminary data suggest that Asian patients with AF might not be the same. Future prospective randomised trials are needed for the selection of NOACs according to different ethnic background.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.
Keywords: Atrial fibrillation; Asians; major bleeding; novel oral anticoagulants; stroke